2019
DOI: 10.3390/microorganisms7030067
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Prebiotics for the Amelioration of Type 1 Diabetes: Present and Future Perspectives

Abstract: Type 1-diabetes (T1D) is an autoimmune disease characterized by immune-mediated destruction of pancreatic beta (β)-cells. Genetic and environmental interactions play an important role in immune system malfunction by priming an aggressive adaptive immune response against β-cells. The microbes inhabiting the human intestine closely interact with the enteric mucosal immune system. Gut microbiota colonization and immune system maturation occur in parallel during early years of life; hence, perturbations in the gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 124 publications
(235 reference statements)
0
66
0
3
Order By: Relevance
“…This is, to the best of our knowledge, a new mechanism by which dietary fiber intake can contribute to lowering of the long list of Western diseases. The lower intake of dietary fiber by consumers in Western countries compared to more traditional societies has been suggested to be one of the major causes of the increasing occurrence of both type 1 and 2 diabetes [47]. Previous studies explained the effects of dietary fiber intake and the lowering of diabetes in consumers as an attenuating effect on inflammatory cells, inhibition of absorption of glucose and fat in the intestine, and increased insulin sensitivity [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…This is, to the best of our knowledge, a new mechanism by which dietary fiber intake can contribute to lowering of the long list of Western diseases. The lower intake of dietary fiber by consumers in Western countries compared to more traditional societies has been suggested to be one of the major causes of the increasing occurrence of both type 1 and 2 diabetes [47]. Previous studies explained the effects of dietary fiber intake and the lowering of diabetes in consumers as an attenuating effect on inflammatory cells, inhibition of absorption of glucose and fat in the intestine, and increased insulin sensitivity [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the synthesis of small-chain fatty acids due to the presence of probiotics seems to be a possible way of influencing the colon homeostasis by activating the free fatty acid receptors involved in regulating the immune system and secreting glucagon-like peptides-1 (GLP-1), which stimulates insulin secretion in pancreatic cells. In this way, autoimmune diseases such as type 1 diabetes can be managed [56].…”
Section: Effect Of Probiotics Strains On Bioavailability Of Functionamentioning
confidence: 99%
“…Probiotics are live microorganisms, which -when administered in adequate amounts -confer a health benefit on the host (12). Probiotics are one of the most accepted strategies to modulate the gut microbiota and normalize dysbiosis (13)(14)(15)(16)(17); therefore, we posit that probiotic therapy can maintain healthy gut microbiota and reduce leaky gut and inflammation. Several preclinical studies have shown that some specific probiotic strains may improve intestinal permeability homeostasis (18,19) and inflammation (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical studies have shown that some specific probiotic strains may improve intestinal permeability homeostasis (18,19) and inflammation (20,21). Multiple studies also suggest that probiotics are beneficial for several human diseases, including obesity and diabetes (13)(14)(15)(16)(17)(21)(22)(23); however, the origin of such probiotics remains largely unknown. Probiotics isolated from a human body source are recommended to be used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%